The power to negotiate : examining mandating procedures in the National Council of Provinces and their impact on legislation and other parliamentary processes - Whittle, Patricia (Department of Public Law, 2016)
This study explores provincial participation and examines (a) how and (b) to what extent negotiating mandates of the respective provinces are taken into account in the legislative processes of Parliament in selected bills in terms of ss 74 and 76 of the Constitution, 1996. It evaluates to what extent current systems, processes, rules and legislation give effect to the will of provinces, as an expression of the views emanating from provincial public participation. The study provides a brief overview of the historic background and evolution of the Parliament of South Africa, followed by a discussion of the constitutional and legislative framework from which the NCOP derives its mandate and a brief comparison of the NCOP to the second chamber of the German Federal Republic, the Bundesrat. The discussion of the Mandating Procedures of Provinces Act, 2008 examines in which ways the Act helps or hinders the mandating processes, drawing on case studies of selected s 76 bills processed before and after the MPPA came into effect. It considers whether the NCOP's public consultation can remedy flawed or inadequate public participation by a department. In the case of constitutional amendment bills that proposes provincial boundary changes, s 74 of the Constitution requires an affected province's approval for such a bill to be passed. It considers whether a constitutional amendment bill can be amended and propose various options for consideration. The conclusion finds that the NCOP gives effect to its constitutional mandate to represent provinces in the legislative and other processes of Parliament with lesser degrees of success in respect of ss74 and 76 bills affecting provinces. It recommends a review and amendment of the MPPA and the NCOP Rules (and where relevant the Joint Rules of Parliament) to enable provinces to have a more meaningful impact on the legislative and other Parliamentary processes involving provinces.